Thematic and intertextual analysis from a feasibility study of the Bonny Method of Guided Imagery and Music with clients in eating disorder treatment - Heiderscheit, Annie (Frontiers in Psychology, 2024)
Eating disorders (ED) are characterized by serious and persistent disturbances with eating, weight control, and body image. Symptoms impact physical health, psychosocial functioning, and can be life-threatening. Individuals diagnosed with an ED experience numerous medical and psychiatric comorbidities due to issues caused by or underlying the ED. Therefore, it is vital to address the complex nature of an ED, as well as the comorbid and underlying issues. This necessitates a psychotherapeutic approach that can help to uncover, explore, and support working through unresolved emotions and experiences. Guided Imagery and Music (GIM) is an in-depth music psychotherapy approach utilizing therapist-programmed music to support the client in uncovering and examining underlying and unresolved issues. The literature surrounding the use of GIM with clients in ED treatment is anecdotal and comprised primarily of clinical case studies. This secondary analysis, based on a descriptive feasibility study that integrated GIM sessions into the client’s regular ED treatment and examined 116 transcripts from a series of sessions of eight clients. Thematic analysis of the transcripts identified nine subthemes and three themes that emerged. These themes include emotional landscape (feeling stuck, acknowledging emotions, and working through unresolved emotions), relationships (self, others, and eating disorders), and transformation and growth (finding strength, change, and empowerment). A short series of GIM sessions helped ED clients identify and address issues underlying the ED and to gain or reclaim a sense of self that enabled them to make choices for their life that support their recovery and sense of empowerment. Intertextual analysis revealed imagery indicative of the Hero’s Journey. Further, how engagement in this embodied aesthetic experience stimulates perceptual, cognitive, and affective brain functions which are key in fostering behavioral and psychological change is explicated as it relates to ED treatment and recovery.